2019
DOI: 10.6007/ijarbss/v9-i6/5971
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Employees’ Tenure and Performance among Middle Managers: The Moderating Role of Psychological Empowerment

Abstract: This study aims to analyses the influence of one important demographic variable, employees' tenure at their organizations towards improving and enhancing employee performance among supervisory level staff in the ceramic tile manufacturing industry. Based on the literature discussed, the role of psychological empowerment will also be studied to see if it has any moderating influence on the relationship between employee's tenure and their performance. Using the quantitative method, the population for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…With respect to tenure of service, Raghavan and Janardhanan (2019), demonstrated in the ceramic tile manufacturing industry, that employees' tenure has a significant influence on their overall performance on the job. This is probably the reason why the study of Ng and Sorensen (2008) showed that workers with longer years of service are highly familiar with the roles and responsibilities of their work and have tendencies to attain the peak of their career on that job than workers with shorter years of experience.…”
Section: Studies On Length Of Service and Team-playing Behaviourmentioning
confidence: 99%
“…With respect to tenure of service, Raghavan and Janardhanan (2019), demonstrated in the ceramic tile manufacturing industry, that employees' tenure has a significant influence on their overall performance on the job. This is probably the reason why the study of Ng and Sorensen (2008) showed that workers with longer years of service are highly familiar with the roles and responsibilities of their work and have tendencies to attain the peak of their career on that job than workers with shorter years of experience.…”
Section: Studies On Length Of Service and Team-playing Behaviourmentioning
confidence: 99%
“…Regression testing was carried out in several stages, including testing the feasibility of the regression model (Goodness of Fit Test), the coefficient of determination (R2), and individual parameter tests. The significance level for each variable was measured at the p-value <0.05 (Cresnar and Nedelko, 2020;Orabi, 2016;Galoji et al, 2013;Raghavan and Janardhanan, 2019).…”
Section: Methodsmentioning
confidence: 99%